2009
DOI: 10.1097/nmd.0b013e3181be78fb
|View full text |Cite
|
Sign up to set email alerts
|

Theory of Mind in Borderline and Cluster-C Personality Disorder

Abstract: Borderline Personality Disorder (BPD) is associated with interpersonal problems, such as intense, unstable relationships and fears of abandonment. It has been hypothesized that deficits in social cognitive capacities explain these difficulties. One important aspect of social cognition is theory of mind (ToM)-the capacity to infer others' mental state. We tested ToM capacities with Happé's advanced ToM-test in 16 BPD patients, 16 Cluster-C PD patient controls, and 28 nonpatients. Social reasoning (WAIS Picture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
55
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 55 publications
7
55
3
Order By: Relevance
“…In one study, male forensic patients with a personality disorder (n = 13; n = 5 BPD subjects and n = 9 subjects with antisocial personality disorder) performed significantly better in the revised RME test and the modified ‘Strange Stories' test than male forensic patients with Asperger's syndrome (n = 13) or schizophrenia (n = 13) [78]. In another study, female patients with BPD (n = 16) had lower ToM test scores than patients with cluster C personality disorder (n = 16) in the ‘Strange Stories' test [67]. When patients with narcissistic and comorbid BPD were excluded, patients with BPD (n = 27; 25 females) showed more impairments in the MASC than patients with narcissistic personality disorder (n = 22; 8 females) [76], which could indicate worse ToM abilities in patients with BPD compared to patients with cluster C personality disorder [67] or narcissistic personality disorder [76].…”
Section: Impaired Empathymentioning
confidence: 99%
See 1 more Smart Citation
“…In one study, male forensic patients with a personality disorder (n = 13; n = 5 BPD subjects and n = 9 subjects with antisocial personality disorder) performed significantly better in the revised RME test and the modified ‘Strange Stories' test than male forensic patients with Asperger's syndrome (n = 13) or schizophrenia (n = 13) [78]. In another study, female patients with BPD (n = 16) had lower ToM test scores than patients with cluster C personality disorder (n = 16) in the ‘Strange Stories' test [67]. When patients with narcissistic and comorbid BPD were excluded, patients with BPD (n = 27; 25 females) showed more impairments in the MASC than patients with narcissistic personality disorder (n = 22; 8 females) [76], which could indicate worse ToM abilities in patients with BPD compared to patients with cluster C personality disorder [67] or narcissistic personality disorder [76].…”
Section: Impaired Empathymentioning
confidence: 99%
“…However, a meta-analysis found only low to moderate correlations between the RME test, the ‘Strange Stories' test, and the ‘Faux Pas' test [66], and results depended on the task and its complexity. Thus, female patients with BPD (n = 16) tended to perform better than healthy women (n = 28) in the ‘Strange Stories' test in which participants have to detect bluffs, mistakes, persuasions, or white lies [67]. In contrast, BPD patients (n = 20; 18 females) showed impaired cognitive ToM abilities in comparison to healthy controls (n = 22; 19 females) in the Understanding ‘Faux Pas' test when they listened to 20 stories and answered questions that detected the occurrence of a faux pas following each story [50].…”
Section: Impaired Empathymentioning
confidence: 99%
“…For example, Russell, Tchanturia, Rahman, and Schmidt (2007) reported a male advantage for Happé's cartoon task, but Bosacki (2000) reported female superiority on a similar task in healthy preadolescents. With respect to BPD, Arntz et al (2009) found enhanced performance of the borderline group relative to nonclinical control subjects on Happé's (1994) Advanced ToM task. Interpretation of these results is severely limited by the relative lack, or absence, of male subjects in most studies of BPD.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in all three studies where empathic skills were examined in interactive social environments, individuals with BPD demonstrated increased abilities to accurately infer mental states and respond appropriately to the behavior of others, relative to control subjects (Flury et al, 2008;Franzen et al, 2011;Ladisich & Feil, 1988). By contrast, in tasks requiring mental state attributions from passive stimuli, individuals with BPD demonstrated enhanced skills in three tests from four studies (Happé's Advanced ToM test, Arntz et al, 2009; RMET for negative emotions only, Scott et al, 2011;overall RMET score, Fertuck et al, 2009 andFrick et al, 2012), conserved skills for three tests from four studies (MSAT, Ghiassi et al, 2010; affective understanding of faux pas, Harari et al, 2010;RMET, Preißler et al, 2010; RMET for positive and neutral emotions, Scott et al, 2011), and reduced skills for two tests from two studies (cognitive understanding of faux pas, Harari et al, 2010;MASC, Preißler et al, 2010). This apparent contrast in results between studies using interactive and passive stimuli suggests that interactive stimuli may be relatively more sensitive in demonstrating the skills of individuals with BPD, and therefore highlights the need for future research to examine borderline social cognition through interactive study environments and relatively realistic social interactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation